Peran Guru dalam Mengatasi Kesulitan Membaca pada Siswa SD - Handayani, Handayani; Adrias, Adrias; Putri Zulkarnaini, Aissy (Pusat Riset dan Inovasi Nasional, 2025)
Reading difficulties in elementary school students are a challenge that needs to be addressed immediately to support their academic development. Teachers have a very important role in identifying, understanding, and providing appropriate interventions for students who experience reading difficulties. This study aims to determine the role of teachers in overcoming reading difficulties in elementary school students, as well as to determine what factors inhibit reading difficulties in elementary school students. The results of the study indicate that teachers play a role in providing individual guidance, implementing various learning strategies, and creating a learning environment that supports the development of students' reading skills. In addition, cooperation between teachers, parents, and other educators also contributes to helping students overcome reading barriers. With a deeper understanding of the strategies implemented by teachers, it is hoped that this study can be a reference for educators in increasing the effectiveness of reading learning in elementary schools.